Socio‑Economic Determinants of Construction Sector Development - Florian Gerth; Martin O’Brien; Karol S. Sikora (SocioEconomic Challenges, 2025)
This study investigates the empirical interaction between changing socioeconomic challenges and the construction sector in Cambodia. The empirical analysis applied uses data from the Statistical Yearbook of Cambodia (2021) to analyze the statistical relationship between socioeconomic , economic, demographic variables and construction. To do this, the study conducts a combination of regression analyses, Ordinary Least Squares in conjunction with Methods-of-Moments, while applying rigor to guarantee compliance with the CLR function assumptions. We find that the link between economic development and activity in construction is more complex than previously believed, with the role of the construction industry changing during economic development. Results show that the number of private dwelling construction projects can be explained by the ratio of primary education (-3.4), number of people employed in the educational sector (13.6), road construction (0.8), and net exports (-0.5). Future research should focus on i) potential endogeneity issues. This might emerge because activity might be conditional on the state of construction which, on the other hand, drives overall activity. ii) disentangling the effects of developments within domestic financial markets and their role in efficiently allocating financial capital to the real economy. Lastly, the significant impact of the Covid-19 crisis on the Cambodian economy, particularly the role of FP (fiscal policy) and MP (monetary policy) and efficient resource allocation within the construction industry. This aspect is crucial, as different industries responded variably to the shock and lock-down caused by Covid-19.